Early vs standard approach to tracheostomy and functional outcome among patients with severe stroke receiving mechanical ventilation: reply - Bösel, Julian; Schönenberger, Silvia; Seder, David (The journal of the American Medical Association, 2022)
In Reply In response to the Letters about SETPOINT2, we agree with Mr Li and Dr Zhou that the location and extent of the brain lesion(s) may be more related to tracheostomy need and timing than the exact vascular pathophysiology. This was in part our rationale for combining the 3 major stroke subtypes in the study population, assuming that by randomization differences in lesion location would be similarly distributed, as was the case between treatment groups. The suggestion to perform a post hoc subgroup analysis according to brain lesion location is appropriate, and that analysis is underway.